Transient electrowetting on dielectric for activating droplets in bioprinting applications - Vo, Xuan-Quoc (2016)
Bio-printing is now facing a big challenge of cell viability with using extrusion based printing or jetting based printing principles. One of the causes is due to the high shear stress and pressure gradient of cell included flows. Digital microfluidics which was activated by electrowetting on dielectrics (EWOD) principles involved potential advantages such as low shear stress induced and high speed activation promisingly overcomes this challenge. Although much efforts has been devoted to understand the phenomenon physically as well as to apply it to activating droplets, there is no complete study about the transient state of EWOD from which it can be used for supporting EWOD based droplet activated system design. This paper will systematically introduce several physical aspects of transient EWOD including dependence of response speed on viscosity and drop’s volume. The results showed that the response speed of droplets strongly depends on drop’s viscosity and size. It also revealed the existence of a critical point of liquid viscosity where the behavior of droplet changes from underdamped to overdamped regimes.